2021
DOI: 10.1002/biof.1760
|View full text |Cite
|
Sign up to set email alerts
|

Cip2A modulates osteogenic differentiation via the ERK‐Runx2 pathway in MG63 cells

Abstract: Cancerous inhibitor of protein phosphatase 2A (Cip2A) is an oncoprotein that promotes the development of several types of cancer. However, its molecular function in osteoblast differentiation remains unclear. In this study, we found that Cip2A was upregulated under osteogenic conditions in MG63 cells. Besides, overexpression of Cip2A significantly increased the expression of Runt‐related transcription factor 2 (Runx2) and alkaline phosphatase (ALP). Inversely, the knockdown of Cip2A in MG63 cells suppressed os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
(51 reference statements)
1
0
0
Order By: Relevance
“… 37 Moreover, many studies have indicated that PP2A is a negative factor in osteoblast differentiation. 38 Consistent with the previous findings, PP2A activity was reduced in OM, SGMS1 overexpression further inhibited PP2A activity, and Cer treatment partially reversed SGMS1 inhibition, thereby reducing PP2A activity. Moreover, SGMS1 knockdown increased PP2A activity that was decreased by OM, and SM treatment again decreased PP2A activity.…”
Section: Discussionsupporting
confidence: 91%
“… 37 Moreover, many studies have indicated that PP2A is a negative factor in osteoblast differentiation. 38 Consistent with the previous findings, PP2A activity was reduced in OM, SGMS1 overexpression further inhibited PP2A activity, and Cer treatment partially reversed SGMS1 inhibition, thereby reducing PP2A activity. Moreover, SGMS1 knockdown increased PP2A activity that was decreased by OM, and SM treatment again decreased PP2A activity.…”
Section: Discussionsupporting
confidence: 91%